The role of CD1a-restricted T cells in the pathogenesis of atopic dermatitis - Jarrett, R (2016)
In recent years, T-cells that recognise lipid ligands presented by CD1 molecules have been described. CD1a is highly expressed by Langerhans cells of the epidermis and it has been shown that CD1a-restricted T-cells circulate at high frequencies, infiltrate the skin and recognise natural skin lipids. Epidermal CD1a- expressing cells are enriched in AD lesions, however pathways associated with CD1a presentation and AD have not been studied. The aim of this project was to investigate the role of CD1a-restricted T-cells in the pathogenesis of AD. The use of target APCs with absent MHC expression (K562 cells) enabled investigation of polyclonal T cell, and HDM responsive CD1a-reactive T cell line responses from many genetically unrelated donors. These T cells were enriched in the blood and skin in patients with AD, and produced a number of cytokines known to be relevant to AD pathogenesis. Using the skin suction blister technique and antigen challenge system, these cells were found to infiltrate human skin following HDM antigen challenge in AD patients. In order to define the underlying mechanisms, we fractionated total HDM extract and found that CD1a reactivity resided within the protein fraction of HDM, which could be explained by HDM-derived secretory phospholipase A2 (sPLA2) activity. T cell responses were dependent on HDM-derived sPLA2, which most likely generates neolipid antigens for presentation via CD1a. T cell lines were also generated to further characterise these cells, and produced a broad range of type 1 and type 2 cytokines on stimulation with HDM and other phospholipase containing allergens. Filaggrin insufficiency is associated with AD and filaggrin was observed to inhibit HDM-derived sPLA2 activity and T cell responses from the blood and skin ex vivo. In summary, the data identify a novel pathway of AD cutaneous inflammation in which HDM-derived sPLA2 generates antigenic neolipids for presentation to CD1a- reactive T cells, and define sPLA2 inhibition as a novel function of filaggrin, with potential therapeutic implications.